Adolfo Caminha e Rodolfo Teófilo: A cidade e o campo na literatura naturalista cearense - Alencar, Manoel Carlos Fonseca de (2002)
This work analyzes how relations between the countryside and the city in Ceará naturalistic literature, but particularly in the works of Adolfo Caminha: No country of the Yankees, A normalist and Temptation; and Rodolfo Teófilo's: Hunger, Paroara and Brilliant and Smallpox and Vaccination in Ceará (...).